Total Body Electrical Conductivity for Determining Carcass Fat in Ruffed Grouse - Aaron B. Proctor; John W. Edwards (National Quail Symposium Proceedings, 2017)
Percent carcass fat is often considered a primary condition indice in game bird species. Although regarded as the standard for determining fat reserves, traditional sampling methods require sacrificing animals for chemical analysis via fat extraction. Lethal methods negate the ability to track condition of individuals through time. Avian physiology studies often require the assessment of conditional changes through time and among various treatments, which necessitate the use of a non-lethal method for estimating fat levels. We were able to accurately estimate fat condition in captive ruffed grouse (Bonasa umbellus) utilizing total body electrical conductivity (TOBEC). We developed predictive models to estimate percent carcass fat directly from first-order regression of TOBEC and body mass values. Validation of our best model from an independent sample (n = 10 individuals) produced an R2 = 0.85(P < 0.001) for determining percent carcass fat and R2 = 0.89(P < 0.001) for determining total fat mass in ruffed grouse. Future studies investigating galliform ecology or physiology could benefit from use of TOBEC for assessment of fat condition if non-lethal sampling is desired to track changes through time.
Keywords: Bonasa umbellus; carcass fat; fat condition; ruffed grouse; TOBEC; total body electrical conductivity